The Metrics of Happiness The Art and Science of Measuring Personal Happiness and Societal Wellbeing - Freeze, R. Allan (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides a comprehensive treatment of how happiness and wellbeing are measured. It presents an accessible summary of the philosophy, methodology, and applicability of the various measurement techniques that have been generated by the leaders of the happiness movement. It traces the history of development of the core ideas, and clarifies the unexpectedly wide range of techniques that are used. The book provides an unbiased assessment of the strengths and weaknesses of each approach and differentiates the contributions that have been made by psychologists, economists, environmentalists, and health scientists. It examines applications at a personal scale, in the workplace, at a societal scale, and on the world stage. It does so in an easy-to-read anecdotal writing style that will appeal to a wide range of academic and lay readers who enjoy popularized non-fiction that address matters of social concern.
Keywords: Quality of life; Well-being.; Social sciences-Statistical methods; Psychometrics; Positive psychology; Quality of Life Research; Well-Being.; Statistics in Social Sciences, Humanities, Law, Education, Behavorial Sciences, Public Policy; Psychometrics; Positive Psychology